Adaptive output feedback control for fractional-order multi-agent systems. (January 2020) - Yang, Zichao; Zheng, Shiqi; Liu, Feng; Xie, Yuanlong
Abstract: This study investigates the leader-following consensus problem in fractional-order multi-agent systems (MAS). First, a distributed observer is presented to estimate the state variables by using only the output information of MAS. Second, to overcome the difficulty of selecting an appropriate Lyapunov function for fractional order MAS, we propose a new state transformation technique to reconstruct the observer dynamic model. Then a new distributed frequency-dependent Lyapunov function is introduced in accordance with this model. Based on this new Lyapunov function, an adaptive vector backstepping controller design procedure is presented. Lastly, a series of virtual signals is generated to compensate for input nonlinearities including dead zones, quantization, and saturation by the fractional order auxiliary systems. Simulation results confirm the validity of the theoretical analysis. Highlights: Leader-following control for heterogeneous fractional order multi-agent systems Output feedback by observer New state transformation technique to reconstruct observer model Adaptive vector backstepping design by distributed frequency-dependent Lyapunov function Auxiliary systems for compensating a larger class of input nonlinearities.